Clinically Significant Improvement in Pre vs Post-Operative PROMIS Scores after Cavovarus Reconstruction in Patients with Charcot-Marie-Tooth Disease. Issue 1 (January 2022) - Haupt, Edward T.; An, Tonya W.; Porter, Giselle M.; Michalski, Max; Pfeffer, Glenn B.
Category: Ankle; Hindfoot; Midfoot/Forefoot; Other Introduction/Purpose: Charcot-Marie-Tooth (CMT) disease is an inherited progressive neurologic disorder characterized by extremity deformities and functional deficits. Surgery is indicated for substantial functional deficits and severe deformity. Reconstructive surgery is individualized and multifaceted to correct the cavovarus deformity, and maximize function with tendon transfers and joint stabilization procedures. No previous study has reported improvement from pre-operative baseline patient reported outcome measures to post-operative outcome measures. We studied PROMIS scores and patient satisfaction surveys to report improvements in physical function, pain interference, and depression. Our hypothesis was that CMT patients' preoperative baseline would be significantly worse than the control population in all domains, and that they would experience demonstrable improvement greater than the minimally clinically important difference (MCID) for the 3 PROMIS score domains tested post- operatively. Methods: Prospective PROMIS scores were collected on 147 feet in 89 patients who had reconstructive foot surgery for CMT during a 40-month period (June 2016-December 2020) by a single surgeon. Radiographic and clinical data were recorded prospectively to identify complications. Each patient completed a battery of physical function (PROMIS-PF), pain interference (PROMIS-PI), and mood/depression (PROMIS-M) instruments pre-operatively, every 3 months for the first post-operative year, and annually thereafter. Pre-operative PROMIS scores are reported for patients prior to any surgery on either foot to establish a functional baseline. Post-operative PROMIS values are reported only after the last planned surgery was completed in the common setting of staged bilateral surgeries. Patient satisfaction surveys were administered at last follow-up. Post-operative complications were recorded. Statistical analysis was performed with students t-test for continuous variables and chi-squared analysis for categorical variables. PROMIS scores are reported as mean (+/- standard deviation). Results: 41 patients met inclusion criteria for reporting pre-operative baseline PROMIS scores, and 57 patient's post-operative PROMIS data were included after the final reconstructive surgery within the study window. Mean follow-up was 26 months. Pre- operative baseline PROMIS demonstrate CMT patients have worse PROMIS-PF, PROMIS-PI, and PROMIS-M than the population which is statistically and clinically significant. All PROMIS domains were improved by clinically and statistically significant values. PROMIS-PF improved from 38 (+/-6) to 46 (+/-5), a 4-5x improvement over MCID (2). PROMIS-PI improved from 59 (+/-8) to 51 (+/-7) representing a 1-2x improvement in the MCID (4). PROMIS M improved from 53 (+/-10) to 49 (+/- 5) achieving MCID 2. >90% were highly satisfied and would undergo surgery again. There were 7 complications: 1 deep infection, 2 superficial infections, 1 superficial wound dehiscence, and 3 unplanned hardware removals. 5/7 of these patients experiencing complications remained 'satisfied' or 'very satisfied'. Conclusion: Patients with CMT disease have baseline functional deficits in physical and mental health as judged by PROMIS measures that were worse than the population means in all 3 tested domains. Surgical reconstruction produced clinically significant improvements in PROMIS-PI, PF, and M domains at up to 4 years of follow-up. Patients were highly satisfied with the results with an acceptable rate of post-operative complications.